The Effect of Males on Birth Weight and Body Weight at 11 Months of Female Friesian Holstein Dairy Cattle At PT. Ultra Ranch South Bandung - Fiqhi Falkan Englan; Lia Budimulyati Salman; Raden Febriyanto Christi (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
This research aims are to identify the birth weight and weight of heifers aged 11 months from each bull that had mate the mother at PT. Ultra Peternakan Bandung Selatan (UPBS). This research used descriptive analysis and one way analysis variance, using SPSS. The data were collected deliberately and in accordance with the completeness of the data, such as pedigree records, livestock identity, names of bulls used, birth weight of heifers, weight of 571 heifers aged 11 months and 22 bulls. The result showed that the average birth weight of heifers (FH) from each bull ranged from 37.78 ± 1.49 kilogram. The average weight of FH aged 11 months from each bull ranged from 302.49 ± 31.73 kilogram. The bull that showed best performance with the highest weight is Coyne PlanetET